Novel characteristics of normal supraspinatus insertion in rats: an ultrastructural analysis using three-dimensional reconstruction using focused ion beam/scanning electron microscope tomography - Kanazawa, Tomonoshin (CIC Edizioni Internazionali, 2014)
BACKGROUND: the histological architecture of the insertion after a rotator cuff repair is completely different from that of normal tendon-bone insertions. Analysis of normal insertions by electron microscopy may enhance the understanding of the pathophysiology of tendon-to-bone healing after rotator cuff repair. The present study examined the normal supraspinatus insertion in rats using a new three-dimensional (3D) electron microscopic method, focused ion beam/scanning electron microscope (FIB/SEM) tomography. METHODS: normal supraspinatus insertion of adult Sprague-Dawley rats was analyzed. FIB/SEM tomography was performed on the entire insertion. The obtained serial images were reconstructed, and the 3D cellular morphology and organization of collagen bundles was observed. RESULTS: the cellular shapes between the tendon-cartilage interface were successfully reconstructed. The cells in the cartilage region were spherical without any cellular processes, while the cells in the intermediate region had some cellular processes oriented longitudinally along the collagen bundles. In addition, these 2 regions were smoothly transferred under ultrastructural resolution. CONCLUSIONS: structures at the normal insertion gradually changed from the fibrous cartilage to the tendon midsubstance, which may contribute to the biomechanical strength of the site. These novel cell characteristics may provide necessary knowledge for better regeneration of tendon-to-bone insertions after rotator cuff repair.